2023
DOI: 10.1038/s41598-023-41112-6
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of gastroparesis in diabetic patients: a systematic review and meta-analysis

Lianxin Li,
Luyao Wang,
Ruolan Long
et al.

Abstract: Although there was no significant heterogeneity in the meta-publication, sensitivity analyses revealed significant heterogeneity. Overall, the prevalence was higher in women (N = 6, R = 4.6%, 95% CI 3.1%, 6.0%, and I2 = 99.8%) than in men (N = 6, R = 3.4%, 95% CI 2.0%, 4.7%, and I2 = 99.6the %); prevalence of type 2 diabetes (N = 9, R = 12.5%, 95% CI 7.7%, 17.3%, and I2 = 95.4%) was higher than type 1 diabetes (N = 7, R = 8.3%, 95% CI 6.4%, 10.2%, and I2 = 93.6%); the prevalence of DGP was slightly lower in DM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This is consistent with the fact that GPER expression in some rodent and human tissues, including pancreatic β-cells, is higher in females than males [12,13]. Ironically, although sex disparities in the burden of GI complications of DM are not well documented, a few studies have reported a higher prevalence of GI complications (particularly gastroparesis) in women than in men with both T1D and T2D [14,15], despite the higher susceptibility of males to diabetes than females. This observation is quite mysterious, and thus, we hypothesize that a detailed understanding of GPER expression and signaling in the GI tissues of diabetic models could help unveil the mystery.…”
Section: Introductionsupporting
confidence: 76%
“…This is consistent with the fact that GPER expression in some rodent and human tissues, including pancreatic β-cells, is higher in females than males [12,13]. Ironically, although sex disparities in the burden of GI complications of DM are not well documented, a few studies have reported a higher prevalence of GI complications (particularly gastroparesis) in women than in men with both T1D and T2D [14,15], despite the higher susceptibility of males to diabetes than females. This observation is quite mysterious, and thus, we hypothesize that a detailed understanding of GPER expression and signaling in the GI tissues of diabetic models could help unveil the mystery.…”
Section: Introductionsupporting
confidence: 76%
“…G-POEM appears to be particularly beneficial for patients with pylorospasm and refractory symptoms not responsive to medical therapy. Despite its potential, further research and long-term follow-up studies are needed to fully establish the efficacy, safety, and patient selection criteria for G-POEM in the management of DGP [19,20].…”
Section: Gastric Peroral Endoscopic Myotomy (G-poem)mentioning
confidence: 99%
“…The clinical presentation of DGP can range from mild to severe symptoms, significantly impairing the quality of life and complicating glycemic control. Diagnosis is primarily based on symptoms and confirmed through gastric emptying studies such as scintigraphy, 13C breath tests, or wireless motility capsules[20]. Management strategies include dietary modifications, glycemic control, pharmacological interventions, and in severe cases, surgical options.…”
mentioning
confidence: 99%
“…A recent meta-analysis looking at the global prevalence of DGP reported an overall prevalence of 9.3%. [ 1 ] The data from the United States indicate that this disease is not very common in North America, which indirectly implies that other areas of the world have a much higher prevalence of gastroparesis. [ 2 ] The prevalence of DGP was reported to be 19% in Brazil, 13.79% in Thailand and an astonishingly high 40% in a study from China.…”
mentioning
confidence: 99%
“…[ 2 ] The prevalence of DGP was reported to be 19% in Brazil, 13.79% in Thailand and an astonishingly high 40% in a study from China. [ 1 ] In a larger study from the UK, Asians formed the second-largest ethnic group among patients with gastroparesis. [ 3 ] The data on DGP from Asian countries, however, are limited.…”
mentioning
confidence: 99%